Prevention of Nosocomial Infection & role of Hand Hygiene Compliance in a Private Hospital of Bangladesh (Bangladesh Critical Care Journal, 2017)
Background: Nosocomial infection (NI) is a major cause of morbidity and mortality of patients attending the healthcare facilities all over the world. Only a few studies regarding this issue have been conducted in Bangladesh.Objective: To describe the load of NI and to assess role of hand hygiene compliance of doctors and nurses regarding its prevention.Method: In this cross-sectional study, medical records of all patients admitted from January 2014 to June 2014 were reviewed and data were collected from patients who had diagnosis of NI. Collected data includes month wise number of NI patients, types of NI, organism responsible for NI and hand hygiene compliance of doctors and nurses. Regarding hand hygiene compliance only critical care areas were considered.Results: During the study period, a total of 8769 patients were admitted in all inpatient departments and critical care areas (cardiac intensive care unit, neonatal intensive care unit, general intensive care unit, coronary care unit, general high dependency unit and cardiac high dependency unit) of the hospital and number of NI was 201 (2.29%). The highest NI was respiratory tract infection (63%) and the lowest was skin & soft tissue infection (2%). Predominant organisms responsible were E. coli (16%), acinetobacter species (15%), Pseudomonas species (14%), Klebsiella species (13%), Serratia species (13%) and Candida species (13%). The highest average hand hygiene compliance (67.67%) and lowest NI (1.14%) was observed in June 2014.Conclusion: In this study, NI rate was the lowest when the hand hygiene compliance was the highest. So, it is obvious that implementation of hand hygiene may be one of the important measures to prevent NI. So, hospitals should have strict guidelines and review measures to prevent this man made phenomenon. All these efforts will not only reduce patient morbidity, but will also reduce the use of antibiotics and healthcare costs of the country.Bangladesh Crit Care J September 2017; 5(2): 83-87